1959
DOI: 10.1121/1.1907712
|View full text |Cite
|
Sign up to set email alerts
|

Intelligibility of Known and Unknown Message Sets

Abstract: The effect of the frequency of occurrence of words upon their intelligibility in noise was examined under two conditions: (1) in unknown message sets where the specific words under test were initially unknown to the listener; and (2) in known message sets where the specific words under test were known to the listener. Substantial effects of word frequency are observed with unknown message sets, but not with known message sets. In known message sets, the prime factor determining intelligibility is the phonemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0

Year Published

1959
1959
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 0 publications
3
38
0
Order By: Relevance
“…For instance, the frequencies of words in common usage influence their thresholds for visual recognition (Pierce, 1963). Other studies have confirmed that highfrequency words are more detectable than low-frequency ones (although memory of high-frequency words presented previously is less accurate) (Broadbent, 1967;Glanzer and Adams, 1985;Glanzer et al, 1993;Pollack et al, 1959). Thus greater familiarity with a stimulus increases its detectability, just as greater uncertainty reduces it.…”
Section: O R R E C T E D P R O O Fmentioning
confidence: 84%
“…For instance, the frequencies of words in common usage influence their thresholds for visual recognition (Pierce, 1963). Other studies have confirmed that highfrequency words are more detectable than low-frequency ones (although memory of high-frequency words presented previously is less accurate) (Broadbent, 1967;Glanzer and Adams, 1985;Glanzer et al, 1993;Pollack et al, 1959). Thus greater familiarity with a stimulus increases its detectability, just as greater uncertainty reduces it.…”
Section: O R R E C T E D P R O O Fmentioning
confidence: 84%
“…Thus, it is possible that the lexical candidates that enter the recognition process may be restricted to the visually present alternatives. Previous research has shown that welldocumented frequency and neighborhood effects in word recognition can be dramatically reduced or even disappear in closed-set tests when all response alternatives are treated as equally probable (Pollack, Rubenstein, & Decker, 1959;Sommers, Kirk, & Pisoni, 1997). Thus, it remains to be established whether the eye-tracking paradigm is sensitive to characteristics of the lexicon that are not directly represented in the set of pictures displayed on a trial.…”
mentioning
confidence: 99%
“…1B). Speech is an ideal stimulus for exploring this relationship because it is well established that listeners rely heavily on both prior knowledge and perceptual learning for successful perception, especially in noisy conditions or when the speech signal is degraded (6,(27)(28)(29)(30)(31)(32)(33). Therefore, using the same stimulus, in the same participants, and in the same experiment, we could test whether these two experience-dependent changes in perception modulate common or dissociable neural mechanisms.…”
mentioning
confidence: 99%